Conceptual and procedural errors of vocational high school students with accounting major in solving inverse functions problems - Ghufroni, Febri Rachmat Al; Rejeki, Sri (AIP conference proceedings, 2023)
Conceptual and procedural understanding is essential in mathematics. However, studies found that students still have problem with it. It can be seen from the errors they made in conceptual and procedural aspects. Therefore, this study aims to analyze students’ misconceptions about solving inverse problems in functions seen from conceptual and procedural errors. This type of research is descriptive and qualitative. The subject of this study was tenth-grade students at a private vocational school with an accounting major in Kartasura, Sukoharjo, Central Java, consisting of 20 students. Written tests and interviews carry out data collection techniques. The data validity uses triangulation techniques by checking the data on the same source with different methods, namely documentation, and interviews. Data analysis techniques involve data reduction, data presentation, and conclusion. Based on the results of data analysis, student ability categories were obtained, namely students with low, medium, and high abilities. The form of conceptual error that students make is that students cannot choose formulas correctly, and students do not master the concept of inverses on functions. The procedural errors made by students are that students do not understand the meaning of the problem, students are wrong in calculating the inverse of functions, and students cannot solve in the simplest form.